Do people make sufficiency-oriented mobile phone choices based on dynamic norms? The perception and effectiveness of sufficiency-promoting messages in online media - Gossen, Maike; Tröger, Josephine; Veneny, Marek; Eichhorn, Henriette; Bergener, Jens (Frontiers in Sustainability, 2023)
Excessive consumption poses a significant threat to the environment. Therefore, overall consumption reduction is necessary. The sufficiency strategy aims to achieve this reduction by enabling individual behavioral changes. In the context of mobile phone choices, one way to promote sufficiency is by encouraging consumers to refrain from purchasing new devices and instead prolong the lifespan of their existing ones. As companies play a major role in shaping products and market conditions that influence consumption, they have a responsibility to support consumers in adopting sufficiencyoriented mobile phone use. However, previous research on the effectiveness of sufficiency-promoting communication and the use of dynamic norms in behavior-change interventions has yielded mixed results. We conducted an online experiment with two specific objectives: First, we examined whether messages emphasizing a dynamic norm have positive impacts on individuals' intentions and behavioral choices regarding sufficiency-oriented mobile phone use. The results indicated no significant effects of a sufficiency-promoting message emphasizing a dynamic norm, compared to two other conditions. Nevertheless, regardless of the message people received, one third of the individuals in all groups chose a sufficiency-oriented voucher. Materialism was found to positively predict both the intention to buy a new mobile phone and sufficiency-oriented behavior, partially contradicting our hypothesis. This suggests that sufficiency-oriented consumption may also be motivated by aspirations for status, albeit in the context of sufficiency. In contrast, personal norms for sufficiency consistently predicted intentions or behaviors aligned with sufficiency, however, not always in the direction we hypothesized. Second, we investigated consumers' attributed motives for online media by comparing a search engine, as an unbiased source of information, with an online store driven by commercial interests. Our analysis revealed significant differences in consumers' perceptions, with altruistic motives attributed to the search engine and exploitative motives attributed to the online store. Our results contribute to the ongoing discussion about the requirements for effective communication strategies that promote sufficiency-oriented choices. We confirm the limited effectiveness of interventions based on dynamic norms in online settings. Nevertheless, our study offers valuables insights for designing future communication initiatives aimed at fostering sufficiency-oriented behaviors.